Miniaturized microscope for non-invasive imaging of leukocyte-endothelial interaction in human microcirculation - Arutyun Bagramyan; Charles P. Lin (Scientific Reports, 2023)
Abstract We present a miniature oblique back-illumination microscope (mOBM) for imaging the microcirculation of human oral mucosa, enabling real-time, label-free phase contrast imaging of individual leukocytes circulating in the bloodstream, as well as their rolling and adhesion on vascular walls—the initial steps in leukocyte recruitment that is a hallmark of inflammation. Using the mOBM system, we studied the leukocyte-endothelial interactions in healthy and locally inflamed tissue and observed drastic changes in leukocyte movement (velocity and displacement profile). Our findings suggest that real-time imaging of leukocyte dynamics can provide new diagnostic insights (assessment of inflammation, temporal progression of disease, evaluation of therapeutic response, etc.) that are not available using conventional static parameters such as cell number and morphology.